Archetype Analysis of the Cinematic Representation of Rajinikanth, the Tamil Film Hero - Prabha, R Rama (Journal of Advanced Research in Journalism & Mass Communication, 2019)
The tropes used by Rajinikanth, the famous Indian Tamil film hero in his films Baasha to Kaala, were analyzed in this research paper. Carl Gustav Jung’s archetypes were used to analyze the heroic representation. The cinematic representation of Rajinikanth in these movies is deliberate and purposeful. He used dual archetypes to attract the attention of the audience. Erel Shallit’s Enemy, Cripple and Beggar: Shadows in the Hero’s Path is used as a model to analyze the archetype adopted by Rajinikanth in his films Baasha to Kaala. He was able to gain political leverage through these depictions. How to cite this article: Prabha RR. Archetype Analysis of the Cinematic Representation of Rajinikanth, the Tamil Film Hero. J Adv Res Jrnl Mass Comm 2019; 6(1): 1-4.